Analysis and control of tundish induction heating power supply using modular multilevel converter. Issue 14 (8th June 2018) - Yue, Yufei; Xu, Qianming; Luo, An; Guo, Peng; He, Zhixing; Li, Yan
Abstract : Modular multilevel converters (MMCs) provide advantages to reach medium‐voltage operation increasing the power level in industrial applications. In this study, a tundish induction heating power supply based MMC (MMC‐TIHPS) is investigated for heating molten steel. The equivalent model of MMC‐TIHPS is established and the energy in horizontal and vertical directions are analysed. The heating control for molten steel consists of temperature increasing and constant temperature processes (alternatively called transient‐state and steady‐state operation). The main contribution of this study is to propose a direct power feedforward control based load current feedforward strategy for TIHPS. With this strategy, TIHPS can be controlled operating with full power to heat molten steel in transient state and guarantee the insulation effectiveness in steady state. Proper parameters of controllers are designed. Experimental results are conducted to validate the feasibility of MMC‐TIHPS and the effectiveness of the proposed control method.